ANALISIS MOTIVASI TERHADAP PENGGUNAAN SISTEM PELAYANAN KARTU BPJS KESEHATAN MASYARAKAT PADA KANTOR BPJS KESEHATAN : Studi Kasus pada BPJS Rantauprapat - Ferry Setiawan; Nurintan Asyiah Siregar (Gapenas Publisher, 2023)
BPJS Kesehatan is the organizer of the social security program in the health sector which is one of the five programs in the National Social Security (SJSN) system, namely Health Insurance, Work Accident Insurance, Old Age Insurance, Pension Insurance, and Death Insurance as stated in Law Number 40 of 2004 concerning the National Social Security System. Every Indonesian citizen and foreigner who has worked in Indonesia for at least six months must become a member of BPJS. This is in accordance with article 14 of the UUBPJS. However, until now, there are still people who do not have the BPJS Kesehatan card. This knowledge aims to find out how the influence of motivation on the use of the BPJS Kesehatan Card Service System. The method used in this study is descriptive quantifiable. Descriptive quantitative is a method that describes the results of research on various variables with actual events. With this method, researchers decipher and analyze the interview results obtained into writings and journals